RESPONSE OF GROWTH, ESSENTIAL OIL CONTENT AND ITS CONSTITUENT'S OF PLECTRANTHUS AMBOINICUS TO IRON AND/OR UREA FOLIAR APPLICATION UNDER SALINE IRRIGATION - Tm, Abdelrazik; As, Sabra; T., Astatkie; Mh, Hegazy; D., Grulova; Hah, Said-al Ahl (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To study the response of Plectranthus amboinicus plants to iron and/or urea foliar application using tap water and Nacl saline water for irrigation, a pot experiment was conducted during two successive seasons (2014 and 2015) under the natural conditions of the greenhouse of the National Research Center, Dokki, Giza, Egypt. Methods: Plectranthus amboinicus cuttings were transplanted in the pots in February of each season. After one month, seedlings were irrigated with (2 levels: Tap water (0.40 dsm-1), and Nacl solution (4 dsm-1)) and FeUrea (4 levels: None, EDTA (200 ppm), urea (1000 ppm), and mixture of urea (1000 ppm) and Fe EDTA (200 ppm)) were applied one month from transplanting. The foliar application treatments were sprayed at 60, 90, 120 and 150 d from transplanting. Plant fresh mass (g/plant) and proline content were determined in the first and second cuts after 120 and 180 d from transplanting, respectively. The essential oil was obtained by hydrodistillation and essential oil % was expressed as ml 100 g/fresh herb. The chemical composition of the essential oil was studied using GC-MS and compounds were identified based on their mass spectra and literature. Results: Repeated measures analysis of the data showed significant effects of irrigation and iron/urea on fresh weight of herb, essential oil (%), oil yield, and proline in both first and second cuts. Plectranthus amboinicus plants sprayed with urea/or iron under tap and Nacl saline conditions were better than the control (unsprayed) plants. While saline irrigation decreased fresh weight, essential oil and oil yield, it increased proline; and 200Fe+1000Urea gave significantly higher proline for both tap and Nacl irrigations. Within each irrigation, the highest fresh mass and oil yield were obtained from 200Fe+1000Urea. Fresh mass for tap irrigation was significantly higher during the second cut than during the first cut, but it was the opposite for oil yield. This research demonstrated that application of iron and/or urea decreases salinity stress, and increases proline content. The GC/MS analysis revealed the major components of Plectranthus amboinicus to be p-cymene, carvacrol, (+)-epibicyclosesquiphellandrene, Î²-cadinene and Î±-cadinol. Conclusion: It may be concluded that Plectranthus amboinicus is tolerant to Nacl irrigations, thus we may recommend its cultivation in slain soil of Egypt. Foliar spraying with iron and/or urea under these conditions could be much more efficient than the not application of nutrients. So, we recommended that foliar application of iron and/or urea to raise the salt stress tolerance of Plectranthus amboinicus.